2021
DOI: 10.1021/jacs.1c06425
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and DNA Damage by Independently Generated 2′-Deoxycytidin-N4-yl Radical

Abstract: Oxidative stress produces a variety of radicals in DNA, including pyrimidine nucleobase radicals. The nitrogencentered DNA radical 2′-deoxycytidin-N4-yl radical (dC•) plays a role in DNA damage mediated by one electron oxidants, such as HOCl and ionizing radiation. However, the reactivity of dC• is not well understood. To reduce this knowledge gap, we photochemically generated dC• from a nitrophenyl oxime nucleoside and within chemically synthesized oligonucleotides from the same precursor. dC• formation is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…1 ) [ 86 ]. In the DNA, oxidative stress can induce several types of damage, including single- and double-strand brakes, DNA-protein crosslinks and base and sugar oxidation products, such as guanine oxidized species (GOS) [ [86] , [87] , [88] ]. A study assessed the presence of GOS in the serum of critical COVID-19 patients from intensive care units [ 56 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…1 ) [ 86 ]. In the DNA, oxidative stress can induce several types of damage, including single- and double-strand brakes, DNA-protein crosslinks and base and sugar oxidation products, such as guanine oxidized species (GOS) [ [86] , [87] , [88] ]. A study assessed the presence of GOS in the serum of critical COVID-19 patients from intensive care units [ 56 ].…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…Chronic inflammation increases the formation of reactive oxygen species (Bartsch and Nair 2004). Oxidative stress can induce various types of damage, including in the double-strand DNA, DNA-protein crosslinks, and oxidation products of sugar groups (Peng et al 2021). Studies have shown that oxidative DNA damage contributes to the development of neurological diseases and several types of cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic in ammation increases the formation of reactive oxygen species [36]. Oxidative stress can induce various types of damage, including in the DNA double-strand, DNA-protein crosslinks, and oxidation products of sugar groups [37]. Studies have shown that oxidative DNA damage contributes to the development of neurological diseases and several types of cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can induce various types of damage, including in the DNA double-strand, DNA-protein crosslinks, and oxidation products of sugar groups [37]. Studies have shown that oxidative DNA damage contributes to the development of neurological diseases and several types of cancer (37,38). DNA damage caused by oxidative stress can be determined by Tail DNA percent levels [40].…”
Section: Discussionmentioning
confidence: 99%